Shohei Imamura le libre penseur - Rocha, Paulo 1935-2012; Kato, Yudai; Bazin, Janine 1923-2003; Labarthe, André S. 1931- (AMIP [u.a.], 1995)
Documentary about the director Shohei Imamura. This intimate portrayal arrives to calm us. In good health and enjoying life, Imamura gets drunk methodically in a bar worthy of "An Autumn Afternoon". Then, in the hands of the professional of an hairdresser, he tells his short experience as a director of pornographic films. We salivate with extracts of unknown and invisible films. We find out he his preparing a new film. It sums up the global project of Imamura perfectly: write the counter-history of Japan, from the point of view of the whores and bandits. [Frédéric Bonnaud, IMDb]
Fernsehmitschnitt: arte 12.04.1995
Keywords: Imamura, Shōhei -- 1926-2006; Biografie